A Signal Model of Wind Turbine Blade Based on Linear Frequency Modulation Signal and Analysis. Issue 4 (June 2019) - Xuchao, Hu; Xiansi, Tan; Zhiguo, Qu
Abstract: Aiming at the interference problem of wind turbine blade to air tube radar, this paper proposes a wind turbine blade echo model based on LFM signal. The model considers the variation characteristics of wind turbine echo signals with blade rotation, establishes the relevant echo amplitude model and phase model, and discusses the electromagnetic scattering characteristics of wind turbine blades under different conditions. The characteristics of wind turbine blade echo signals in time domain, frequency domain and time-frequency domain are studied by using the proposed model. The influence of wind turbine blades on radar signal processing is analysed. Simulations demonstrate the effectiveness of the signal model.